The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1097/md.0000000000032304
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of single- and multiple-antenna microwave ablation for the treatment of hepatocellular carcinoma and liver metastases: A systematic review and network meta-analysis

Abstract: Background: There is a myriad of microwave ablation (MWA) systems used in clinical settings worldwide for the management of liver cancer that offer a variety of features and capabilities. However, an analysis on which features and capabilities result in the most favorable efficacy and safety results has never been completed due to a lack of head-to-head comparisons. The aim of this study is to compare single-antenna and multiple-antenna MWA using radiofrequency ablation (RFA) as a common comparator … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…The possibility to obtain very large ablation zones (larger than 6 cm) by means of the triple‐antenna approach in association with reliable repositioning under CT guidance has also been reported 27 . A recently published meta‐analysis showed that multiple‐antenna MW ablation has the best results in terms of complete ablation rate at 1 month and local tumour progression‐free, 3‐year overall survival (OS), and major complications, and is the optimal technology for tumours ≥2 cm in diameter 28 . Simultaneous multiple‐antenna MW ablation is able to improve heat distribution, with higher temperatures reached peripherally, and reduce the occurrence of clefting, which often arises when repositioning a single antenna and leads to sunken tissue between two sequential ablation zones 28,29 .…”
Section: How To Improve Local Efficacy Of Thermal Ablationmentioning
confidence: 96%
See 2 more Smart Citations
“…The possibility to obtain very large ablation zones (larger than 6 cm) by means of the triple‐antenna approach in association with reliable repositioning under CT guidance has also been reported 27 . A recently published meta‐analysis showed that multiple‐antenna MW ablation has the best results in terms of complete ablation rate at 1 month and local tumour progression‐free, 3‐year overall survival (OS), and major complications, and is the optimal technology for tumours ≥2 cm in diameter 28 . Simultaneous multiple‐antenna MW ablation is able to improve heat distribution, with higher temperatures reached peripherally, and reduce the occurrence of clefting, which often arises when repositioning a single antenna and leads to sunken tissue between two sequential ablation zones 28,29 .…”
Section: How To Improve Local Efficacy Of Thermal Ablationmentioning
confidence: 96%
“…27 A recently published metaanalysis showed that multiple-antenna MW ablation has the best results in terms of complete ablation rate at 1 month and local tumour progression-free, 3-year overall survival (OS), and major complications, and is the optimal technology for tumours ≥2 cm in diameter. 28 Simultaneous multiple-antenna MW ablation is able to improve heat distribution, with higher temperatures reached peripherally, and reduce the occurrence of clefting, which often arises when repositioning a single antenna and leads to sunken tissue between two sequential ablation zones. 28,29 These factors may contribute to lower rates of local tumour recurrence and increased treatment efficacy.…”
Section: Multiple Electrode/antennas Positioningmentioning
confidence: 99%
See 1 more Smart Citation
“…[8][9][10] However, this procedure often leads to hyperthermia-induced side effects on important organs adjacent to the lesion undergoing ablation. [11][12][13] Therefore, it is necessary to explore and develop novel treatment technologies to address these challenges.…”
Section: Introductionmentioning
confidence: 99%